The use of Latent Profile Analyses to examine social dominance orientation as a predictor of peer-to-peer aggression among adolescents - Gumpel, Thomas P. (Journal of interpersonal violence, 2023)
Peer-to-peer aggression and bullying is a social phenomenon and is related to social structures in the school. In-group membership as well as construction of the other and differentiation from other potential groups is an important predictor of one’s social identity. Social Dominance Orientation is an important addition to social identity theory as it examines both issues of social dominance and social egalitarianism and is related to out-group denigration. In this study, we examined whether social dominance theory (both the dominance and egalitarian forms) will add to the prediction of physical and relational aggression among adolescents. Using a bias-corrected 3-step approach, we used Latent Profile Analyses to examine the responses of 1617 Israeli adolescents on measures of social dominance and egalitarian orientation, salience of their social groups and moral disengagement. Based on the analysis, we identified four classes of respondents, which can be broken down into two distinct categories: high social dominance and moral disengagement and high social egalitarianism. We compared male and female adolescent respondents and group salience. We then compared the four latent profiles on the two distal variables of physical and relational peer-to-peer aggression. Findings have theoretical and applied relevance to further investigating issues of group dynamics and construction of the other as potential predictive factors in understanding peer-to-peer aggression and bullying.